2017
DOI: 10.1002/jor.23501
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the optimum source of mesenchymal stem cells for use in knee surgery

Abstract: Single sitting procedures where the mononuclear cell fraction is extracted from bone marrow and implanted directly into cartilage and bone defects are becoming more popular as novel treatments for cartilage defects which have, until now had few treatment options. This is on the basis that the mesenchymal stem cells (MSCs) contained within will repair the damaged tissue. This study sought to determine if the femur and tibia could provide equivalent amounts of mesenchymal stem cells, with equivalent viability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
3
22
0
1
Order By: Relevance
“…Commonly used sites include the iliac crest, distal femur, proximal tibia, proximal humerus and the calcaneus. Authors have reported that bone marrow aspirate taken from the posterior iliac crest has the highest concentration of BM-MSCs 46–49. There are at least eight commercially available systems that can be used to harvest bone marrow aspirate, all of which require 30 mL at a minimum, but preferably 60 mL 22.…”
Section: Bone Marrow Aspirate Concentratementioning
confidence: 99%
“…Commonly used sites include the iliac crest, distal femur, proximal tibia, proximal humerus and the calcaneus. Authors have reported that bone marrow aspirate taken from the posterior iliac crest has the highest concentration of BM-MSCs 46–49. There are at least eight commercially available systems that can be used to harvest bone marrow aspirate, all of which require 30 mL at a minimum, but preferably 60 mL 22.…”
Section: Bone Marrow Aspirate Concentratementioning
confidence: 99%
“…Aside from age-mismatch between cohorts, an additional potential limitation of our study is difference in MSC origin between patients with MS and control subjects. Notably, however, pelvic marrow is generally accepted as the gold standard for isolation of MSCs [43] . That the control cohort had osteoarthritis could be a possible additional confounding effect, although, aside from age-related effects, there have been no consistent reports of the effects of osteoarthritis on isolation and proliferation of MSCs from femoral shaft marrow [44] , [45] , [46] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow aspirate concentrate is the term used to describe the MSCs and marrow elements obtained from bone marrow aspiration. The posterior iliac crest is most commonly used, since it has been shown to provide the highest concentration of MSCs . The aspirate must undergo density gradient centrifugation to isolate progenitor cells because they account for a small population of the cells within bone marrow (0.001% to 0.01%) .…”
Section: Orthobiologics and The Literaturementioning
confidence: 99%
“…The posterior iliac crest is most commonly used, since it has been shown to provide the highest concentration of MSCs. 32 The aspirate must undergo density gradient centrifugation to isolate progenitor cells because they account for a small population of the cells within bone marrow (0.001% to 0.01%). 33 BMAC has been shown to serve as a source for growth factors such as platelet-derived growth factor, TGF-b, and bone morphogenetic protein 2, which have anabolic and anti-inflammatory effects.…”
Section: Mesenchymal Signaling Cellsmentioning
confidence: 99%